Dynamic changes in targeted phenolic compounds and antioxidant potency of carob fruit (Ceratonia siliqua L.) products during in vitro digestion - Goulas, Vlasios; Hadjisolomou, Andriani (My University, 2019)
Carob fruit is considered as a rich source of phenolics that are linked with potent health effects. The aim of this work was to study the effect of a triple-step digestion on the stability of phenolics and antioxidant potency in carob products. Results showed that the gastric and intestinal steps induced the most significant changes in the stability of pure phenolics; their recovery ranged between 61 and 88% at oral, 40–87% at gastric and 16–57% at intestinal step. Regarding to the carob products, the yield of phenolic contents were ranged from 0.83 to 1.41 for gastric and from 0.43 to 0.82 for intestinal phase. The counterpart yield of antioxidant potency was 0.84–1.66 and 0.48–0.67, respectively. HPLC analysis also disclosed interesting findings; the stability of phenolics is strongly influenced by their chemical structure. In general, the phenolic acids are quite resistant under digestion procedure, whereas the flavonols are mostly degraded when they were subjected into digestion. Results points out that the carob phenolics are degraded, released from food matrix or attached to other food or digestive juice constituents. Furthermore, the critical role of food matrix was underlined as the food components had a protective effect against pH changes and enzymatic activities along digestion.
Keywords: Antioxidant activity; Carob fruit; Ceratonia siliqua L; Flavonoids; Phenolic acids